The role of the antioxidant system and the photosynthetic behavior of paraquat-resistant Conyza sumatrensis in Brazil - Pereira, Vinicius G. C. [UNESP]; Carbonari, Caio A. [UNESP]; Silva, Marcelo A. [UNESP]; Costa, Renato N. [UNESP]; Krenchinski, Fabio H. [UNESP]; Bevilaqua, Natalia C. [UNESP]; Velini, Edivaldo D. [UNESP] (Taylor & Francis, 2023)
Greenhouse experiments were carried out aiming to characterize—morphologically and biochemically—resistant and susceptible plants of C. sumatrensis. Two experiments were carried out to evaluate the behavior of morphological variables such as leaf area, height, and dry biomass weight, without application of paraquat (1,1'-dimethyl-4,4'-bipyridinium dichloride). Other experiments were conducted with two rates of paraquat application (0 and 800 g a.i ha−1); physiological variables were assessed at 2, 4, and 24 h after application (HAA), and plants were collected at 4 HAA for biochemical analyses of antioxidant enzymes and cell membrane peroxidation level. Without herbicide application, paraquat-resistant populations had higher dry biomass, leaf area, liquid photosynthetic rate, carboxylation efficiency, and stomatal conductance. The recovery of the photosynthetic apparatus by resistant plants after paraquat application is rapid (16 HAA) and, in general, presents physiological improvements in terms of photosynthetic rate and carboxylation efficiency. After paraquat treatment, the antioxidant system enzymes of resistant plants showed increased activity and decreased membrane peroxidation, indicating that these enzymes play an important role in the resistance mechanism of these plants.
Keywords: Oxidative stress; photosystem I inhibitors; reactive oxygen species; sumatran fleabane